Pengaruh Penambahan Abu Batubara Terhadap Hasil Uji Kompaksi (Studi Kasus Tanah Lempung Toraja Utara) - Gerwin Kevin Bumbungan; John Patanduk; Irwan Lie Keng Wong (Paulus Civil Engineering Journal, 2020)
Soil is the basis of a building structure. Each area has varied soil characteristics and properties. Often there are some poor and less favorable soil properties for building construction. Examples of soil properties that need to be considered are high plasticity, low shear strength, compressibility, or changes in volume and swelling big shrinkage. It is very important to know the soil problem and make efforts to fix it. This test aims to determine the addition of fly ash to the soil, as well as to determine the value of soil moisture content in soil compaction testing (proctor compaction) after mixing fly ash. From the results of soil compaction testing, the soil stabilized with fly ash at variations of 0%, 10%, 15%, 20%, and 25% indicates an increase in the value of dry density. In the soil compaction test by mixing fly ash, the dry density value of the variation of 0% was 1.307 and increased to 25% of 1.379